Multidimensional assessment of child welfare for Tanzania - Channing Arndt; Vincent Leyaro; Kristi Mahrt; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
We contribute to the literature on trends in living standards in Tanzania by analysing child welfare using two multi-dimensional approaches, first-order dominance (FOD) and Alkire-Foster (AF). Between 1991/92 and 2010, remarkably similar area rankings emerge that suggest a widening gap between the best and worst performing areas with the majority of areas lying in a tight range in the middle. The methodologies also complement each other by providing upper and lower bounds on underlying welfare dynamics. While both methods point to overall improvements since 1991/92, AF suggests a consistent trend while FOD suggests periods of advance and stagnation.
Keywords: D63; I3; I32; O55; 330; multidimensional poverty; Tanzania; welfare